2004
DOI: 10.21273/horttech.14.3.0437
|View full text |Cite
|
Sign up to set email alerts
|

Why Master Gardeners Stop Volunteering: Lack of Time

Abstract: ADDITIONAL INDEX WORDS. consumer horticulture, training volunteers, volunteer retentionSUMMARY. Nearly 300 Master Gardeners (MGs) who stopped volunteering were surveyed as to why they did not continue in the program. The fi vequestion survey was mailed to people who had not turned in volunteer hours for the previous two years. Forty-seven percent or 131 useable surveys were returned and tabulated. A majority of the respondents, 73 (56%), indicated "no time" as the primary reason for not volunteering. Illness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Typically, 300 Master Gardener interns are trained each year while at the same time 300 previously active Master Gardeners exit the program. Meyer (2004) stated that more than a quarter of Master Gardeners in the Minnesota program left due to dislike or disappointment with the program, or failure to acquire enough horticulture education. Haynes and Trexler (2003) found that organizations must be cognizant of the quality and scope of training programs to ensure that the training meets volunteers' needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, 300 Master Gardener interns are trained each year while at the same time 300 previously active Master Gardeners exit the program. Meyer (2004) stated that more than a quarter of Master Gardeners in the Minnesota program left due to dislike or disappointment with the program, or failure to acquire enough horticulture education. Haynes and Trexler (2003) found that organizations must be cognizant of the quality and scope of training programs to ensure that the training meets volunteers' needs.…”
Section: Discussionmentioning
confidence: 99%
“…Master Gardeners associate with the program for two main reasons: to increase horticultural knowledge and to help their community (Schrock et al, 2000b). Disappointment with the program and insufficient horticulture education have been cited as reasons for not continuing with the program (Meyer, 2004). Coordinating horticultural education with the interests of volunteers is important in increasing retention.…”
Section: T He Master Gardener Program Was Launched In Washingtonmentioning
confidence: 99%
“…A large number of volunteers remain active in the program for many years because they perceive many personal benefits of the program, including the personal value of the horticultural knowledge gained through the program, the perception of prestige, and the flexibility in the volunteer service activities conducted and completed (Meyer, 2007;Schrock et al, 2000;Takle et al, 2016). However, retention of participants is a concern within the MG program because many members do not remain active (Meyer, 2004;Stouse and Marr, 1992;Takle et al, 2016).…”
mentioning
confidence: 99%